DAMPAK KEBIJAKAN B30 TERHADAP NILAI PERUSAHAAN INDUSTRI MINYAK SAWIT DALAM PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) 2030 - Fairuz Nadhifah; Elis Rahmawati Mar'atus Sholihah; Ngani Alwirya Musi; Titin Andriyani Atmojo; Cicik Retno Wati (Program Studi Ekonomi Pembangunan, 2026)
This study examines the relationship between ROA, ROE, DER, and ownership of ISPO/RSPO certificates on the firm value of palm oil companies listed on the Indonesia Stock Exchange (2022-2024). Using quantitative explanatory methods, 11 companies were analyzed through multiple regressions after classical assumption tests. The study employs four independent variables: X1 (ROA), X2 (ROE), X3 (DER), and X4 (ownership of ISPO and RSPO certificates), and one dependent variable (firm value). The results show that ROA has a positive and significant effect on firm value. Conversely, ROE has a negative and significant effect. DER shows a positive but insignificant effect, while ownership of ISPO and RSPO certificates has a negative and significant effect on firm value. Although the B30 policy has the potential to support SDGs targets and strategies through emission reduction and economic growth, the impact of certification on firm value remains negative due to high certification costs and the lack of market incentives. The implications of this study emphasize the need for financial incentives (subsidies or tax allowances), national campaigns to create premium prices, and the strengthening of certification governance. This study is limited by its short observation period and limited sample size, so generalization should be made cautiously.